Case study: Problematics of implementing differentiation learning in Kediri city - Nurfianto, Dwi Muhamad; Saidah, Karimatus; Primasatya, Nurita (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
This research aims to describe the obstacles faced by teachers in implementing differentiated learning in Kediri City. SDN Sukorame 2 Kediri City was chosen as the research location because it has implemented differentiated learning since the 2021/2022 school year. The type of research used is qualitative research with a case study research design. The subjects of this research were nine sources consisting of grade 1, 2, 4 and 5 teachers as well as the principal of SDN Sukorame 2 Kediri City. Data collection techniques through observation, interviews and documentation studies. Based on the findings, it shows implementation obstacles such as lack of teacher understanding and knowledge regarding the concept of differentiated learning, difficulty in preparing differentiated teaching modules, difficulty identifying individual student learning needs, difficulty providing a variety of learning materials, limited energy and time, lack of time allocation in learning. , as well as difficulties in classroom management.